A high-strength and high-weather-resistant ecological permeable brick and its preparation method
Through the combination of ceramic particle clusters and doped TiO2 phase, the problems of insufficient strength, weatherability and water permeability of permeable bricks are solved, and new permeability of high-strength, high weatherability and high water permeability are realized, which is suitable for sponge urban construction. , has the advantages of environmentally friendly and economical benefits.
Patent Information
- Application Number
- CN202410875056.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-01
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2044-07-01
AI Technical Summary
The existing permeable bricks have shortcomings in strength, weather resistance and water permeability, which makes it difficult for them to meet the needs of high strength and long-term use in sponge city construction.
The method of combining ceramic particle clusters and doped TiO2 is used to prepare ceramic particle clusters by spray granulation and sintering at high temperatures. The strength and weather resistance are improved by using Al2O3 particles and nanorods, TiO2 particles and micro whiskers. Improve water permeability and self-cleaning performance.
It significantly improves the strength, weather resistance and water permeability of permeable bricks, extends the service life, reduces production costs, and realizes the resource utilization and environmentally friendly characteristics of waste.
Smart Images

Figure CN118812246B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of permeable bricks, and in particular to a high-strength and high-weather-resistant ecological permeable brick and a preparation method thereof. Background Art
[0002] With the acceleration of urbanization, the construction of sponge cities has gradually entered the people's vision and become the core strategy of urban development. The core concept of sponge cities is to closely integrate the natural tap water circulation mechanism of the city with urban construction through the application of advanced materials, so as to achieve the effective collection, purification and reuse of rainwater, and then effectively prevent and alleviate urban waterlogging disasters. In this process, high-strength and high-weather-resistant ecological permeable bricks have become an indispensable building material. First of all, sponge cities require large-scale permeable building materials to ensure that rainwater can quickly penetrate into the ground. Therefore, ecological permeable bricks must have high strength to withstand the frequent loads of vehicles and pedestrians while maintaining their stable permeability. Secondly, given that ecological permeable bricks will be exposed to a changing outdoor environment for a long time, such as extreme weather such as sunshine, wind and rain, their weather resistance is particularly critical. Only by passing strict weather resistance tests to ensure that bricks can maintain excellent performance in long-term use can the stringent requirements of sponge city construction be met. In summary, high-strength and high-weather-resistant ecological permeable bricks play a vital role in the construction of sponge cities. They not only help the rapid infiltration of rainwater and reduce the risk of urban waterlogging, but their high strength and weather resistance also ensure the stability and reliability of bricks in long-term use. Therefore, the construction of sponge cities has increasingly highlighted the demand for high-strength and high-weather-resistant ecological permeable bricks, providing a broad space for their application and development.
[0003] At present, the development of permeable bricks has made great progress, but there are still some shortcomings: (1) Insufficient strength. The strength problem cannot be ignored. Permeable bricks often use lightweight materials such as sand and stone powder. The natural strength of these materials is limited. In addition, the problems that may exist in the manufacturing process, such as insufficient brick pressing force and improper sintering temperature, further weaken their strength. (2) Insufficient weather resistance. Permeable bricks are easily eroded by natural factors such as weathering and corrosion in the long-term natural environment, resulting in a decrease in weather resistance. This may be related to the insufficient optimization of the material composition and surface treatment technology of permeable bricks, making it difficult to effectively resist erosion and damage from the natural environment. (3) Permeability needs to be improved. The current permeable bricks may have unreasonable aspects in the pore structure design, such as uneven pore distribution and the use of barren aggregates (such as stones), which limits their permeability and makes it impossible to achieve the ideal permeability effect. Therefore, permeable bricks still face many challenges in terms of strength, weather resistance and permeability. In order to fill this technological gap, it is necessary to develop a new type of permeable brick that has the properties of high strength, high weather resistance and high permeability to meet the needs of permeable bricks. Summary of the invention
[0004] (1) Technical issues solved
[0005] The purpose of the present invention is to provide a high-strength and high-weather-resistant ecological permeable brick and a preparation method thereof, so as to solve the problems of insufficient strength, weather resistance and water permeability of the current permeable bricks.
[0006] (2) Technical solution
[0007] In order to achieve the above object, the present invention provides the following technical solutions:
[0008] A high-strength and high-weather-resistant ecological permeable brick is made of the following components by weight: 80 to 120 parts of ceramic particle clusters, 5 to 15 parts of sintering aids, 2 to 4 parts of polyvinyl alcohol, and 20 to 45 parts of tap water;
[0009] The high-strength and high-weather-resistant ecological permeable brick is composed of ceramic particle clusters and doped TiO2 phases;
[0010] The ceramic particle clusters consist of ceramic particles and Al2O3 phases;
[0011] The Al2O3 phase is in the form of a mixture of Al2O3 microblocks and Al2O3 nanorods, and the Al2O3 phase combines the ceramic particles together to form ceramic particle clusters;
[0012] The average particle size of the ceramic particles is 12 to 50 μm;
[0013] The ceramic particles are obtained by crushing, high-energy ball milling and screening waste ceramic bricks in sequence;
[0014] The average diameter of the ceramic particle clusters is 1 to 8 mm;
[0015] The doped TiO2 phase exists in the form of a mixed morphology of micro-blocks and micron whiskers, combining ceramic particle clusters to form high-strength and high-weather-resistant ecological permeable bricks.
[0016] The doping element of the doped TiO2 is Fe element;
[0017] The doped TiO2 phase is formed in situ by the sintering aid at high temperature;
[0018] The preparation method of the sintering aid comprises the following steps: adding 20 to 45 parts of titanate, 1 to 3 parts of siderite and 15 to 25 parts of tap water into a container by weight, then gradually adding 1 mol / L HCl solution into the container, stopping the addition when the pH value of the solution is 1.5 to 4, then evaporating the solution to obtain a dry white product, washing the white product with tap water for 3 times, wherein the tap water completely submerges the white product during each washing process, and finally drying to obtain the sintering aid.
[0019] The preparation method of the titanate is as follows: by weight, 50 to 80 parts of high-titanium slag, 5 to 10 parts of NaOH and 200 parts of tap water are mixed evenly and added into a stainless steel reactor, heated to 220 to 260° C., kept warm for 2 to 4 hours, filtered, washed with tap water until the filtered product is neutral, and finally dried to obtain the titanate.
[0020] The high-strength and high-weather-resistant ecological permeable brick has a porosity of 25-35%, a splitting tensile strength of 6.8-7.6 MPa, and a water permeability coefficient of 4.5-8×10 -2 cm / s, compressive strength is 55-85MPa, and wear-resistant wear pit length is 18.4-19.7mm.
[0021] The present invention also provides a method for preparing a high-strength and high-weather-resistant ecological permeable brick, comprising the following steps:
[0022] S1: Preparation of ceramic particles: The waste ceramic bricks are crushed and high-energy ball-milled in sequence, and then the ceramic particles with an average particle size of 12 to 50 μm are sieved for use.
[0023] S2: Preparation of ceramic particle clusters: The ceramic particles obtained in S1 are prepared into a ceramic slurry, and then a ceramic particle cluster green body is obtained by a spray granulation method, and then a primary sintering is performed at a high temperature to obtain a ceramic particle cluster.
[0024] S3: Preparation of sintering aid: First, titanate is prepared using high-titanium slag, NaOH and 200 parts of tap water as raw materials, and then a sintering aid is prepared using titanate, siderite, tap water and HCl solution as raw materials.
[0025] S4: Preparation of fired permeable bricks: After uniformly mixing ceramic particle clusters, sintering aids, polyvinyl alcohol and tap water, put them into a mold for pressing to obtain permeable brick blanks, and then perform secondary sintering after drying to obtain high-strength and high-weather-resistant ecological permeable bricks.
[0026] Furthermore, the preparation method of the ceramic slurry in step S2 is: by weight, 80 to 120 parts of ceramic particles, 5 to 15 parts of polyvinyl alcohol adhesive, 15 to 30 parts of AlCl3, 5 to 10 parts of NaOH, 2 to 6 parts of sodium dodecylbenzene sulfonate, 1 to 3 parts of nickel chloride and 10 to 20 parts of tap water are mixed evenly to obtain a ceramic slurry.
[0027] Furthermore, the mass ratio of AlCl3 to NaOH is 3:1.
[0028] Furthermore, the parameters of the spray granulation method of the ceramic slurry in step S2 are: the spray granulation inlet temperature is 220-280°C, the outlet temperature is 200-220°C, the rotation speed of the centrifugal atomizer is 2500-9000r / min, and the drying chamber temperature is 210-280°C.
[0029] Furthermore, the parameters of the initial sintering in step S2 are: the ceramic particle cluster green body is sintered in an air atmosphere using a pressureless sintering technology, the temperature is raised from room temperature to 180-240° C. and kept for 1-2 hours, and then the temperature is continued to be raised to 900-1000° C. and sintered for 3-6 hours to obtain a ceramic particle cluster.
[0030] Furthermore, the parameters of the secondary sintering in step S4 are: pressureless sintering, a sintering temperature of 1150-1300° C., a sintering time of 5-10 hours, and cooling to room temperature after sintering to finally obtain high-strength and high-weatherability ecological permeable bricks.
[0031] This study aims to prepare high-performance permeable bricks by introducing Al2O3 particles and nanorods into ceramic particle clusters. This strategy is mainly based on the following synergistic effects: First, the chemical compatibility between in-situ self-generated Al2O3 and ceramic particles promotes the formation of tight chemical bonds, thereby significantly enhancing the overall strength of the ceramic particle clusters. The high mechanical strength of Al2O3 ceramics itself, combined with Al2O3 particles and nanorods as reinforcing phases, greatly improves the strength of permeable bricks. Secondly, nano-alumina nanorods are synthesized at high temperature by nickel chloride catalysis, and their nano-size effect and surface interface effect are used to effectively enhance the strength and toughness of permeable bricks. Nanorods, as reinforcing phases, can effectively block crack propagation, thereby significantly improving the overall strength of ceramic particle clusters. Furthermore, this study constructs a tight and stable microstructure by finely regulating the connection process between Al2O3 particles and nanorods and ceramic particles, effectively reducing the gaps and cracks between particles, and further improving the overall strength and stability of ceramic particle clusters. In terms of weather resistance, the excellent chemical stability and corrosion resistance of Al203 ceramics, as well as the excellent protective properties provided by nano-alumina materials, together provide ceramic particle clusters with strong resistance to a variety of molten metals and chemicals. This protective mechanism forms a dense protective film on the surface of the ceramic particles, which effectively resists the erosion of harmful substances in the external environment and significantly extends the service life of the ceramic particle clusters. In addition, the strong connection between Al203 particles and nanorods and ceramic particles not only enhances the binding force between particles, but also improves the resistance of ceramic particle clusters to cracking and loosening when subjected to external forces, thereby significantly improving their weather resistance. In summary, this study successfully prepared high-strength, high-weather-resistant ceramic particle cluster permeable bricks by synergistically utilizing the excellent properties of Al203 ceramics and nano-alumina materials, combined with the connection between particles, providing an important reference for the performance improvement of permeable bricks and the expansion of material application fields.
[0032] The purpose of preparing ceramic clusters by spray granulation method in the present invention is to improve the water permeability and strength of permeable bricks. The spray granulation method can spray powdered ceramic materials into spherical particle clusters, and then unite these ceramic particles together to form ceramic clusters by sintering or other methods. This preparation method can make the particle distribution of ceramic clusters more uniform, thereby improving the water permeability and strength of permeable bricks. Uniformly distributed ceramic clusters can increase the porosity and pore size distribution uniformity of permeable bricks. The water permeability of permeable bricks depends on the pore structure inside them, and the uniform distribution of ceramic clusters can provide more channels and pores, making it easier for tap water to penetrate. In addition, the uniform distribution of particles can also avoid large particle agglomeration and pore blockage, further improving the water permeability of permeable bricks. At the same time, the uniformly distributed ceramic clusters can provide a more uniform force transmission path, enhancing the overall strength and compressive resistance of permeable bricks. When the permeable bricks are subjected to external loads, the ceramic clusters play a supporting and strengthening role. If the distribution of clusters is uneven, clusters in some areas are subjected to greater forces, while other areas are subjected to less force, which can easily lead to cluster rupture and destruction. Uniformly distributed ceramic clusters can provide a more uniform force transmission path, reduce local stress concentration, and enhance the overall strength and compressive resistance of permeable bricks. In summary, the permeability and strength of permeable bricks can be improved by preparing ceramic clusters by spray granulation. The uniform distribution of ceramic clusters can increase the porosity and uniformity of pore size distribution of permeable bricks and improve the permeability. At the same time, uniformly distributed clusters can provide a more uniform force transmission path and enhance the overall strength and compressive resistance of permeable bricks. This new type of permeable brick has broad application prospects in urban construction and environmental protection.
[0033] In this study, high-performance permeable bricks with multiple synergistic effects were successfully prepared by linking ceramic particle clusters with doped TiO2 particles and doped TiO2 micro whiskers. First, doped TiO2 significantly enhances the structural stability of ceramic particle clusters with its high hardness and excellent mechanical properties, and greatly improves the compressive, bending and tensile strength of permeable bricks by forming a multi-level reinforcement structure. At the same time, the excellent adhesion of doped TiO2 effectively strengthens the bonding force between ceramic clusters, further improving the overall strength of permeable bricks. Secondly, the introduction of doped TiO2 particles and micro whiskers significantly improves the self-cleaning performance of permeable bricks. As a photocatalytic material, TiO2 can catalytically decompose organic matter, bacteria and pollutants on the surface under ultraviolet light to achieve self-cleaning. The combination of particles and micro whiskers provides a larger reaction surface area for permeable bricks, and due to its unique morphology and size effect, it can more effectively capture and decompose pollutants, maintain the long-term clean and beautiful appearance of permeable bricks, and reduce cleaning and maintenance costs. In terms of weather resistance, doped TiO2 provides strong protection for permeable bricks with its excellent weather resistance and chemical stability. Doped TiO2 particles and micro whiskers form a protective layer on the surface of permeable bricks, which effectively blocks the erosion of external pollutants and harmful gases and prolongs the service life of permeable bricks. In addition, this study also explored the dual role of siderite in the preparation process. Siderite not only acts as a catalyst to guide the growth of TiO2 micro whiskers, improves crystal quality and crystallinity, but also is added to TiO2 as a dopant to enhance its photocatalytic performance. Doped TiO2 has higher light absorption capacity and photocatalytic activity, which further improves the self-cleaning performance of permeable bricks. Finally, the high temperature resistance of doped TiO2 enables permeable bricks to resist damage from unexpected situations such as fire, significantly improving their safety and durability. In summary, this study successfully prepared a new type of permeable brick with high strength, high self-cleaning and high weather resistance by doping TiO2 particles and micro whiskers and the synergistic effect of siderite. This new type of permeable brick has broad application prospects in urban construction and environmental protection, and is of great significance for promoting urban sustainable development.
[0034] The present invention obtains ceramic particle clusters and high-temperature sintering aids from waste ceramic bricks and high-titanium slag respectively, and has the following advantages. First, obtaining ceramic particle clusters and high-temperature sintering aids through waste ceramic bricks and high-titanium slag can improve the utilization rate of resources and achieve the goal of waste utilization. Secondly, waste ceramic bricks and high-titanium slag usually pollute the environment, and this invention can convert them into useful products, reduce environmental load, and have environmentally friendly characteristics. In addition, ceramic particle clusters have a wide range of applications and can be used to make ceramic products, thereby creating more ceramic products to meet market demand. At the same time, the sintering properties of ceramics can be improved by obtaining high-temperature sintering aids, so that they have better physical and chemical properties. Finally, this invention can reduce the cost of raw materials, improve production efficiency, and bring significant economic benefits. In summary, this invention has important application value and market prospects in waste utilization, environmental protection, resource conservation and economic benefits.
[0035] (3) Beneficial technical effects
[0036] This study first successfully prepared high-performance permeable bricks by introducing Al2O3 particles and nanorods into ceramic particle clusters. This preparation method is based on the chemical compatibility between Al2O3 and ceramic particles, which effectively enhances the overall strength of the clusters. At the same time, nano-alumina rods, as a reinforcing phase, significantly improve the strength and toughness of permeable bricks. By finely regulating the connection process between Al2O3 particles and nanorods and ceramic particles, we constructed a tight and stable microstructure, further improving the weather resistance and external force resistance of permeable bricks. In addition, we used spray granulation to prepare ceramic clusters to make the particle distribution more uniform, which not only improved the permeability and strength of permeable bricks, but also increased the uniformity of its porosity and pore size distribution. Next, this study further prepared high-performance permeable bricks with multiple synergistic effects by doping TiO2 particles and micro whiskers to link ceramic particle clusters. The high hardness and excellent mechanical properties of TiO2 significantly enhanced the structural stability of ceramic particle clusters and improved the compression, bending and tensile properties of permeable bricks. At the same time, the photocatalytic properties of TiO2 give the permeable brick excellent self-cleaning performance, effectively reducing maintenance costs. In this process, siderite, as a catalyst and dopant, not only guides the growth of TiO2 micro whiskers, improves the crystal quality and crystallinity, but also enhances the photocatalytic performance of TiO2, further improving the self-cleaning performance of the permeable brick. In addition, the weather resistance and high temperature resistance of doped TiO2 enable the permeable brick to maintain stable performance in harsh environments and extend its service life. It is worth mentioning that this study also uses waste ceramic bricks and high-titanium slag as raw materials, and prepares ceramic particle clusters and high-temperature sintering aids through reasonable treatment. This approach not only improves the utilization rate of resources and achieves the goal of waste utilization, but also reduces environmental pollution and embodies the characteristics of environmental friendliness. At the same time, the wide application of ceramic particle clusters provides more possibilities for the development of the ceramic industry and meets market demand. The introduction of high-temperature sintering aids effectively improves the sintering properties of ceramics, giving them better physical and chemical properties. In summary, this study has achieved significant improvements in the strength, weather resistance, permeability and self-cleaning properties of permeable bricks through the innovative combination of materials and processes, and has demonstrated significant synergistic effects. This type of permeable high-performance brick has broad application prospects in urban construction and environmental protection, and is of great significance for promoting sustainable urban development. At the same time, this study also demonstrated its significant value in waste utilization, environmental protection, resource conservation and economic benefits, providing strong support for the development of urban construction and environmental protection. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 This is the XRD analysis spectrum of the ceramic particles prepared in Example 1 of the present invention.
[0038] Figure 2 This is the XRD analysis spectrum of the ceramic particle cluster phase prepared in Example 1 of the present invention.
[0039] Figure 3 This is the XRD analysis spectrum of the permeable brick phase prepared in Example 1 of the present invention.
[0040] Figure 4 This is a morphology picture of the ceramic particle clusters prepared in Example 1 of the present invention.
[0041] Figure 5 This is a morphology diagram of the permeable brick prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0042] To make the purpose, technical solution and advantages of the embodiments of the present invention more clear, the technical solution in the embodiments of the present invention will be clearly and completely described below in conjunction with the accompanying drawings in the embodiments of the present invention.
[0043] In the absence of specific conditions, the operations in the examples are carried out under conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used, if the manufacturer is not indicated, are all common products on the market. Parts not mentioned in the technical content of the present invention will be processed with reference to the prior art. Unless otherwise specified, the following examples and comparative examples will be tested in parallel and use the same processing steps and parameters. Table 1 shows the reagents required for the examples and comparative examples and the corresponding purchasing companies.
[0044] Reagents company Polyvinyl alcohol Shandong Mantanghong New Materials Co., Ltd. Tap water Guangdong Wengjiang Chemical Reagent Co., Ltd. High titanium slag Fuxin Jiuxing Titanium Industry Co., Ltd. NaOH Shanghai MacLean Biochemical Technology Co., Ltd. Siderite Tonghua Iron and Steel Group Dalizi Mining Co., Ltd. HC1 Shandong West Asia Chemical Co., Ltd. Sodium dodecylbenzenesulfonate Himaclin Biochemical Technology Co., Ltd. Nickel chloride Guangzhou Haoyu International Trade Co., Ltd.
[0045] Example 1
[0046] A high-strength and high-weather-resistant ecological permeable brick is made of the following components by weight: 80 parts of ceramic particle clusters, 5 parts of sintering aids and 2 parts of polyvinyl alcohol, and 20 parts of tap water; the high-strength and high-weather-resistant ecological permeable brick is composed of ceramic particle clusters and doped TiO2 phases; the ceramic particle clusters are composed of ceramic particles and Al2O3 phases; the Al2O3 phase is a mixed morphology of Al2O3 microblocks and Al2O3 nanorods, and the Al2O3 phase combines the ceramic particles together to form ceramic particle clusters;
[0047] The average particle size of the ceramic particles is 12 μm; the ceramic particles are obtained by crushing, high-energy ball milling and screening of waste ceramic bricks;
[0048] The average diameter of the ceramic particle clusters is 1mm; the doped TiO2 phase exists in the form of a mixture of micro-blocks and micron whiskers, combining the ceramic particle clusters to form high-strength and high-weatherability ecological permeable bricks; the doping element of the doped TiO2 is Fe; the doped TiO2 phase is a sintering aid that is self-generated in situ at high temperature;
[0049] The preparation method of the sintering aid is as follows: by weight, 50 parts of high-titanium slag, 5 parts of NaOH and 200 parts of tap water are mixed evenly and added to a stainless steel reactor, heated to 220°C, kept warm for 2 hours, then filtered, the filtered product is washed with tap water until the washing liquid is neutral, and finally dried to obtain titanate; 20 parts of titanate, 1 part of siderite and 15 parts of tap water are added to a container, and then 1 mol / L HCl solution is gradually added to the container, and the addition is stopped when the pH of the solution is 1.5, and then the solution is evaporated to obtain a dry white product, and the white product is washed 3 times with tap water, and the tap water completely submerges the white product during each washing process, and finally dried to obtain a sintering aid.
[0050] The present invention also provides a method for preparing a high-strength and high-weather-resistant ecological permeable brick, comprising the following steps:
[0051] S1: Preparation of ceramic particles: The waste ceramic bricks are crushed and high-energy ball-milled in sequence, and then the ceramic particles with an average particle size of 12 μm are sieved for use.
[0052] S2: Preparation of ceramic particle clusters: The ceramic particles obtained in S1 are prepared into a ceramic slurry, and then a ceramic particle cluster blank is obtained by spray granulation, and then the ceramic particle cluster is initially sintered at a high temperature. The preparation method of the ceramic slurry is as follows: 80 parts of ceramic particles, 5 parts of polyvinyl alcohol adhesive, 15 parts of AlCl3, 5 parts of NaOH, 2 parts of sodium dodecylbenzene sulfonate, 1 part of nickel chloride and 10 parts of tap water are mixed evenly by weight to obtain a ceramic slurry. The parameters of the spray granulation method of the ceramic slurry are as follows: the spray granulation inlet temperature is 220°C, the outlet temperature is 200°C, the speed of the centrifugal atomizer is 2500r / min, and the drying chamber temperature is 210°C. The parameters of the initial sintering are as follows: the ceramic particle cluster blank is sintered in an air atmosphere using a pressureless sintering technology, the temperature is raised from room temperature to 180°C for 1h, and then the temperature is continued to rise to 900°C for sintering for 3h to obtain a ceramic particle cluster.
[0053] S3: Preparation of sintering aid: First, titanate is prepared using high-titanium slag, NaOH and tap water as raw materials, and then a sintering aid is prepared using titanate, siderite, tap water and HCl solution as raw materials.
[0054] S4: Preparation of fired permeable bricks: After evenly mixing ceramic particle clusters, sintering aids, polyvinyl alcohol and tap water, put them into a mold and press-form them to obtain permeable brick blanks. After drying, they are sintered for the second time to obtain high-strength and high-weather-resistant ecological permeable bricks. The parameters of the secondary sintering are: pressureless sintering, sintering temperature of 1150°C, sintering time of 5h, and after sintering, cool to room temperature to finally obtain high-strength and high-weather-resistant ecological permeable bricks.
[0055] Example 2
[0056] A high-strength and high-weather-resistant ecological permeable brick is made of the following components by weight: 90 parts of ceramic particle clusters, 8 parts of sintering aids and 3 parts of polyvinyl alcohol, and 25 parts of tap water; the high-strength and high-weather-resistant ecological permeable brick is composed of ceramic particle clusters and doped TiO2 phases; the ceramic particle clusters are composed of ceramic particles and Al2O3 phases; the Al2O3 phase is a mixed morphology of Al2O3 microblocks and Al2O3 nanorods, and the Al2O3 phase combines the ceramic particles together to form ceramic particle clusters;
[0057] The average particle size of the ceramic particles is 20 μm; the ceramic particles are obtained by crushing, high-energy ball milling and screening waste ceramic bricks in sequence;
[0058] The average diameter of the ceramic particle clusters is 4 mm; the doped TiO2 phase exists in the form of a mixture of micro-blocks and micron whiskers, combining the ceramic particle clusters to form high-strength and high-weatherability ecological permeable bricks; the doping element of the doped TiO2 is Fe; the doped TiO2 phase is a sintering aid that is self-generated in situ at high temperature;
[0059] The preparation method of the sintering aid is as follows: in parts by weight, 60 parts of high-titanium slag, 7 parts of NaOH and 200 parts of tap water are mixed evenly and added to a stainless steel reactor, heated to 230°C, kept warm for 3 hours, then filtered, and the filtered product is washed with tap water until the washing liquid is neutral, and finally dried to obtain titanate; 25 parts of titanate, 2 parts of siderite and 20 parts of tap water are added to a container, and then 1 mol / L HCl solution is gradually added to the container, and the addition is stopped when the pH of the solution is 2, and then the solution is evaporated to obtain a dry white product, and the white product is washed 3 times with tap water. During each washing process, the tap water completely submerges the white product, and finally dried to obtain a sintering aid.
[0060] The present invention also provides a method for preparing a high-strength and high-weather-resistant ecological permeable brick, comprising the following steps:
[0061] S1: Preparation of ceramic particles: The waste ceramic bricks are crushed and high-energy ball-milled in sequence, and then the ceramic particles with an average particle size of 20 μm are sieved out for use.
[0062] S2: Preparation of ceramic particle clusters: The ceramic particles obtained in S1 are prepared into a ceramic slurry, and then a ceramic particle cluster blank is obtained by spray granulation, and then the ceramic particle cluster is initially sintered at a high temperature to obtain a ceramic particle cluster. The preparation method of the ceramic slurry is as follows: 90 parts of ceramic particles, 10 parts of polyvinyl alcohol adhesive, 21 parts of AlCl3, 7 parts of NaOH, 3 parts of sodium dodecylbenzene sulfonate, 2 parts of nickel chloride and 14 parts of tap water are mixed evenly by weight to obtain a ceramic slurry. The parameters of the spray granulation method of the ceramic slurry are as follows: the spray granulation inlet temperature is 240°C, the outlet temperature is 205°C, the speed of the centrifugal atomizer is 4500r / min, and the drying chamber temperature is 250°C. The parameters of the initial sintering are as follows: the ceramic particle cluster blank is sintered in an air atmosphere using a pressureless sintering technology, the temperature is raised from room temperature to 1200°C for 1h, and then the temperature is continued to rise to 920°C for sintering for 4h to obtain a ceramic particle cluster.
[0063] S3: Preparation of sintering aid: First, titanate is prepared using high-titanium slag, NaOH and tap water as raw materials, and then a sintering aid is prepared using titanate, siderite, tap water and HCl solution as raw materials.
[0064] S4: Preparation of fired permeable bricks: After evenly mixing ceramic particle clusters, sintering aids, polyvinyl alcohol and tap water, put them into a mold and press-formed to obtain a permeable brick blank. After drying, secondary sintering is performed to obtain a high-strength and high-weather-resistant ecological permeable brick. The parameters of the secondary sintering are: pressureless sintering, a sintering temperature of 1200°C, a sintering time of 7h, and after sintering, the temperature is cooled to room temperature to finally obtain a high-strength and high-weather-resistant ecological permeable brick.
[0065] Example 3
[0066] A high-strength and high-weather-resistant ecological permeable brick is made of the following components by weight: 110 parts of ceramic particle clusters, 12 parts of sintering aids and 3 parts of polyvinyl alcohol, and 35 parts of tap water; the high-strength and high-weather-resistant ecological permeable brick is composed of ceramic particle clusters and doped TiO2 phases; the ceramic particle clusters are composed of ceramic particles and Al2O3 phases; the Al2O3 phase is a mixed morphology of Al2O3 microblocks and Al2O3 nanorods, and the Al2O3 phase combines the ceramic particles together to form ceramic particle clusters;
[0067] The average particle size of the ceramic particles is 40 μm; the ceramic particles are obtained by crushing, high-energy ball milling and screening waste ceramic bricks in sequence;
[0068] The average diameter of the ceramic particle clusters is 6mm; the doped TiO2 phase exists in the form of a mixture of micro-blocks and micron whiskers, combining the ceramic particle clusters to form high-strength and high-weatherability ecological permeable bricks; the doping element of the doped TiO2 is Fe; the doped TiO2 phase is a sintering aid that is self-generated in situ at high temperature;
[0069] The preparation method of the sintering aid is as follows: by weight, 70 parts of high-titanium slag, 8 parts of NaOH and 200 parts of tap water are mixed evenly, added to a stainless steel reactor, heated to 250°C, kept warm for 3 hours, then filtered, and the filtered product is washed with tap water until the washing liquid is neutral, and finally dried to obtain titanate; 40 parts of titanate, 2 parts of siderite and 20 parts of tap water are added to a container, and then 1 mol / L HCl solution is gradually added to the container, and the addition is stopped when the pH of the solution is 3, and then the solution is evaporated to obtain a dry white product, and the white product is washed 3 times with tap water. During each washing process, the tap water completely submerges the white product, and finally dried to obtain a sintering aid.
[0070] The present invention also provides a method for preparing a high-strength and high-weather-resistant ecological permeable brick, comprising the following steps:
[0071] S1: Preparation of ceramic particles: The waste ceramic bricks are crushed and high-energy ball-milled in sequence, and then the ceramic particles with an average particle size of 40 μm are sieved out for use.
[0072] S2: Preparation of ceramic particle clusters: The ceramic particles obtained in S1 are prepared into a ceramic slurry, and then a ceramic particle cluster blank is obtained by spray granulation, and then the ceramic particle cluster is initially sintered at a high temperature. The preparation method of the ceramic slurry is as follows: 110 parts of ceramic particles, 12 parts of polyvinyl alcohol adhesive, 24 parts of AlCl3, 8 parts of NaOH, 5 parts of sodium dodecylbenzene sulfonate, 2 parts of nickel chloride and 18 parts of tap water are mixed evenly by weight to obtain a ceramic slurry. The parameters of the spray granulation method of the ceramic slurry are as follows: the spray granulation inlet temperature is 270°C, the outlet temperature is 210°C, the speed of the centrifugal atomizer is 8000r / min, and the drying chamber temperature is 260°C. The parameters of the initial sintering are as follows: the ceramic particle cluster blank is sintered in an air atmosphere using a pressureless sintering technology, the temperature is raised from room temperature to 220°C for 2h, and then the temperature is continued to rise to 980°C for sintering for 5h to obtain a ceramic particle cluster.
[0073] S3: Preparation of sintering aid: First, titanate is prepared using high-titanium slag, NaOH and tap water as raw materials, and then a sintering aid is prepared using titanate, siderite, tap water and HCl solution as raw materials.
[0074] S4: Preparation of fired permeable bricks: After evenly mixing ceramic particle clusters, sintering aids, polyvinyl alcohol and tap water, put them into a mold and press-form them to obtain permeable brick blanks. After drying, they are sintered for the second time to obtain high-strength and high-weather-resistant ecological permeable bricks. The parameters of the secondary sintering are: pressureless sintering, sintering temperature of 1250°C, sintering time of 8h, and after sintering, cool to room temperature to finally obtain high-strength and high-weather-resistant ecological permeable bricks.
[0075] Example 4
[0076] A high-strength and high-weather-resistant ecological permeable brick is made of the following components by weight: 120 parts of ceramic particle clusters, 15 parts of sintering aids and 4 parts of polyvinyl alcohol, and 45 parts of tap water; the high-strength and high-weather-resistant ecological permeable brick is composed of ceramic particle clusters and doped TiO2 phases; the ceramic particle clusters are composed of ceramic particles and Al2O3 phases; the Al2O3 phase is a mixed morphology of Al2O3 microblocks and Al2O3 nanorods, and the Al2O3 phase combines the ceramic particles together to form ceramic particle clusters;
[0077] The average particle size of the ceramic particles is 50 μm; the ceramic particles are obtained by crushing, high-energy ball milling and screening of waste ceramic bricks;
[0078] The average diameter of the ceramic particle clusters is 8mm; the doped TiO2 phase exists in the form of a mixture of micro-blocks and micron whiskers, combining the ceramic particle clusters to form high-strength and high-weatherability ecological permeable bricks; the doping element of the doped TiO2 is Fe; the doped TiO2 phase is a sintering aid that is self-generated in situ at high temperature;
[0079] The preparation method of the sintering aid is as follows: 80 parts of high-titanium slag, 10 parts of NaOH and 200 parts of tap water are mixed evenly by weight, added to a stainless steel reactor, heated to 260°C, kept warm for 4 hours, filtered, and the filtered product is washed with tap water until the washing liquid is neutral, and finally dried to obtain titanate; 45 parts of titanate, 3 parts of siderite and 25 parts of tap water are added to a container, and then 1 mol / L HCl solution is gradually added to the container, and the addition is stopped when the pH of the solution is 4, and then the solution is evaporated to obtain a dry white product, and the white product is washed 3 times with tap water. During each washing process, the tap water completely submerges the white product, and finally dried to obtain a sintering aid.
[0080] The present invention also provides a method for preparing a high-strength and high-weather-resistant ecological permeable brick, comprising the following steps:
[0081] S1: Preparation of ceramic particles: The waste ceramic bricks are crushed and high-energy ball-milled in sequence, and then the ceramic particles with an average particle size of 50 μm are sieved out for use.
[0082] S2: Preparation of ceramic particle clusters: The ceramic particles obtained in S1 are prepared into a ceramic slurry, and then a ceramic particle cluster blank is obtained by spray granulation, and then the ceramic particle cluster is initially sintered at a high temperature. The preparation method of the ceramic slurry is as follows: 120 parts of ceramic particles, 15 parts of polyvinyl alcohol adhesive, 30 parts of AlCl3, 10 parts of NaOH, 6 parts of sodium dodecylbenzene sulfonate, 3 parts of nickel chloride and 20 parts of tap water are mixed evenly by weight to obtain a ceramic slurry. The parameters of the spray granulation method of the ceramic slurry are as follows: the spray granulation inlet temperature is 280°C, the outlet temperature is 220°C, the speed of the centrifugal atomizer is 9000r / min, and the drying chamber temperature is 280°C. The parameters of the initial sintering are as follows: the ceramic particle cluster blank is sintered in an air atmosphere using a pressureless sintering technology, the temperature is raised from room temperature to 240°C for 2h, and then the temperature is continued to rise to 1000°C for sintering for 6h to obtain a ceramic particle cluster.
[0083] S3: Preparation of sintering aid: First, titanate is prepared using high-titanium slag, NaOH and tap water as raw materials, and then a sintering aid is prepared using titanate, siderite, tap water and HCl solution as raw materials.
[0084] S4: Preparation of fired permeable bricks: After evenly mixing ceramic particle clusters, sintering aids, polyvinyl alcohol and tap water, put them into a mold and press-formed to obtain a permeable brick blank. After drying, secondary sintering is performed to obtain a high-strength and high-weather-resistant ecological permeable brick. The parameters of the secondary sintering are: pressureless sintering, a sintering temperature of 1300°C, a sintering time of 10h, and after sintering, the temperature is cooled to room temperature to finally obtain a high-strength and high-weather-resistant ecological permeable brick.
[0085] Example 5
[0086] The method is basically the same as Example 1, except that the average particle size of the prepared ceramic particles is 50 μm. The porosity of the obtained high-strength and high-weather-resistant ecological permeable brick is 28%, and the water permeability coefficient is 5.5×10 -2 cm / s, and the compressive strength is 78MPa.
[0087] Example 6
[0088] The method is basically the same as Example 1, except that the average diameter of the prepared ceramic particle clusters is 8 mm. The porosity of the obtained high-strength and high-weather-resistant ecological permeable brick is 32%, and the water permeability coefficient is 7×10 -2 cm / s, and the compressive strength is 80MPa.
[0089] Comparative Example 1
[0090] The method is basically the same as Example 1, except that the catalyst nickel chloride is not added in the preparation of ceramic particle clusters in step S2.
[0091] Comparative Example 2
[0092] The method is basically the same as Example 1, except that no siderite is added in the step S3 of preparing the sintering aid.
[0093] Characterization Tests:
[0094] The present invention uses a scanning electron microscope (SEM) to observe the microstructure of the permeable brick in detail. First, a representative sample is selected from the prepared permeable brick, and after drying and gold spraying, it is placed in the sample chamber of the scanning electron microscope. Under the high magnification of the scanning electron microscope, the microstructure inside the permeable brick can be clearly observed, including the size, shape, distribution of the pores, and the connection between the pores. This information is of great significance for evaluating the permeability, mechanical properties and durability of the permeable brick.
[0095] The present invention also uses X-ray diffraction (XRD) technology to characterize the microstructure of the permeable brick and its preparation process. At the key stages of the preparation process, such as raw material mixing, molding, sintering, etc., the corresponding samples are selected for XRD testing. By analyzing the test results, the mineral phase composition, crystal structure, and possible phase changes in the sample can be determined. This information not only helps to understand the impact of the preparation process of the permeable brick on the microstructure, but also provides an important basis for optimizing the preparation process. In addition, by XRD testing the finished permeable brick, the stability and durability of its microstructure can be further verified.
[0096] Figure 1 This is the XRD analysis spectrum of the ceramic particles prepared in Example 1 of the present invention. It can be seen from the figure that the ceramic particles are mainly composed of feldspar and mullite; Figure 2 This is the XRD analysis spectrum of the ceramic particle cluster phase prepared in Example 1 of the present invention. From the figure, it can be seen that in addition to feldspar and mullite, aluminum oxide also exists, proving that aluminum oxide is the bonding agent of the ceramic particles; Figure 3 The XRD analysis spectrum of the permeable brick phase prepared in Example 1 of the present invention shows that titanium dioxide phase exists in the permeable brick, proving that the phase converted by the sintering aid is titanium dioxide.
[0097] Figure 4 This is a morphology of the ceramic particle cluster prepared in Example 1 of the present invention. It can be seen that aluminum oxide sticks the ceramic particles together in the form of micro-blocks and nano-rods. Figure 5 The morphology of the permeable brick prepared in Example 1 of the present invention shows that titanium dioxide whiskers exist between the ceramic particle clusters.
[0098] Performance Test:
[0099] Porosity: The porosity of permeable bricks is measured using the Archimedes drainage method.
[0100] Compressive strength: When evaluating the compressive strength of permeable bricks, we strictly follow the relevant provisions and requirements of the national standard for "Permeable Pavement Bricks and Permeable Road Panels" (GB / T 25993-2010). These standards provide us with clear and standardized testing procedures and evaluation criteria, ensuring the accuracy and reliability of compressive strength tests. By following these standards, we can comprehensively and objectively evaluate the compressive performance of permeable bricks, providing strong guarantees for practical applications.
[0101] Splitting tensile strength: refer to GB / T25993-2010 splitting tensile strength test method.
[0102] Water permeability: When evaluating the water permeability of permeable bricks, we use the water permeability coefficient as the key indicator and strictly follow the specific requirements of the national standard "Permeable Pavement Bricks and Permeable Pavement Panels" (GB / T 25993-2010) to conduct tests. This standard provides us with standardized test methods and clear evaluation criteria to ensure that the water permeability of permeable bricks can be accurately and reliably evaluated. By following these specifications, we can better understand the water permeability of permeable bricks and provide more accurate data support for practical applications.
[0103] Freeze-thaw resistance: When evaluating the frost resistance of permeable bricks, we use the number of freeze-thaw cycles as the core indicator, and this evaluation is strictly carried out in accordance with the specific provisions of Appendix G Freeze-thaw Resistance Test Method of JG / T376-2012 "Sand-based Permeable Bricks". This standard provides us with standardized testing procedures and clear evaluation criteria to ensure accurate and reliable evaluation of the frost resistance of permeable bricks. Following these specifications, we can have a more comprehensive understanding of the performance of permeable bricks in cold environments and provide strong technical support for practical applications. After the frost resistance test, the surface of the permeable bricks with sticky skin, defects, missing edges and corners, cracks, color difference and delamination are considered qualified. In addition, the strength loss rate before and after antifreeze and the mass loss rate of a single block are used to evaluate the stability and durability of the permeable bricks under extreme climatic conditions. Such results provide us with a strong guarantee to ensure that the permeable bricks can withstand the test of freeze-thaw cycles in practical applications.
[0104] Wear resistance: Based on the special method for measuring the length of wear pits of permeable bricks in the GB / T 12988 standard, this standardized process ensures that we can accurately measure the performance of permeable bricks after being subjected to friction and wear, thereby evaluating their wear resistance.
[0105] The performances of the permeable bricks of Examples 1 to 6 and Comparative Examples 1 to 2 are summarized in Table 2.
[0106] Table 2 Performance of permeable bricks in Examples 1 to 6 and Comparative Examples 1 to 2
[0107]
[0108]
[0109] The main difference between Example 1 and Comparative Example 1 is whether the catalyst nickel chloride is added in the preparation of the ceramic particle clusters. The ceramic particle clusters prepared by adding nickel chloride contain alumina nanorods. It can be clearly seen from Table 2 that the addition of nickel chloride can significantly improve the compressive strength, splitting tensile strength, freeze-thaw resistance and wear resistance of the permeable bricks.
[0110] The main difference between Example 1 and Comparative Example 2 is whether siderite is added in step S3 to prepare the sintering aid. It can be seen from Table 2 that the permeable bricks after adding siderite have titanium oxide whiskers, so the compressive strength, freeze-thaw resistance, splitting tensile strength and wear resistance of the permeable bricks are significantly improved.
[0111] The high-strength weather-resistant permeable brick prepared by the present invention has a splitting tensile strength of 6.8-7.6 MPa and a water permeability coefficient of 4.5-8×10 -2 cm / s, compressive strength is 55-85MPa, wear pit length is 18.4-19.7mm, frost resistance (D25): mass loss rate is 0.5-0.7%, strength loss rate is 4.5-5%, which fully meets the requirements of GB / T25993-2010 "Permeable Pavement Bricks and Permeable Pavement Panels". Its specific indicators are: a. Splitting tensile strength ≥4.0MPa; b. Permeability coefficient ≥1.0×10 -2 cm / s; c. Wear resistance: wear pit length ≤35mm; e. Frost resistance (D25): mass loss rate ≤5%, strength loss rate ≤20%.
[0112] In summary, the present invention introduces Al2O3 particles and nanorods into ceramic particle clusters and TiO2 particles and micron whiskers into permeable bricks, and combines the utilization of waste ceramic bricks and high-titanium slag to successfully prepare high-performance permeable bricks with high strength, high weather resistance and excellent permeability, which is of great significance to promoting urban sustainable development and resource conservation.
[0113] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the above embodiments, ordinary technicians in the relevant field should understand that all equivalent structural changes made under the concept of the present invention and using the contents of the present invention specification and drawings should be covered within the scope of protection of the claims of the present invention.
Claims
1. A high-strength and high-weather-resistant ecological permeable brick, characterized in that: The method is prepared from the following components by weight: 80 to 120 parts of ceramic particle clusters, 5 to 15 parts of sintering aids, 2 to 4 parts of polyvinyl alcohol, and 20 to 45 parts of tap water; The high-strength and high-weather-resistant ecological permeable brick is composed of ceramic particle clusters and doped TiO2 phases; The ceramic particle clusters consist of ceramic particles and Al2O3 phases; The Al2O3 phase is in the form of a mixture of Al2O3 microblocks and Al2O3 nanorods, and the Al2O3 phase combines the ceramic particles together to form ceramic particle clusters; The average particle size of the ceramic particles is 12 to 50 μm; The ceramic particles are obtained by crushing, high-energy ball milling and screening waste ceramic bricks in sequence; The average diameter of the ceramic particle clusters is 1 to 8 mm; The doped TiO2 phase exists in the form of a mixture of micro-blocks and micron whiskers, combining ceramic particle clusters to form high-strength and high-weather-resistant ecological permeable bricks; The doping element of the doped TiO2 is Fe element; The doped TiO2 phase is formed in situ by the sintering aid at high temperature; The preparation method of the sintering aid comprises the following steps: adding 20 to 45 parts of titanate, 1 to 3 parts of siderite and 15 to 25 parts of tap water into a container by weight, then gradually adding 1 mol / L HCl solution into the container, stopping the addition when the pH value of the solution is 1.5 to 4, then evaporating the solution to obtain a dry white product, washing the white product with tap water for 3 times, wherein the tap water completely submerges the white product during each washing process, and finally drying to obtain the sintering aid.
2. A high-strength and high-weather-resistant ecological permeable brick as claimed in claim 1, characterized in that: The preparation method of the titanate is as follows: by weight, 50 to 80 parts of high-titanium slag, 5 to 10 parts of NaOH and 200 parts of tap water are mixed evenly and added into a stainless steel reactor, heated to 220 to 260° C., kept warm for 2 to 4 hours, filtered, washed with tap water until the filtered product is neutral, and finally dried to obtain the titanate.
3. A high-strength and high-weather-resistant ecological permeable brick as claimed in claim 1, characterized in that: The high-strength and high-weather-resistant ecological permeable brick has a porosity of 25-35%, a splitting tensile strength of 6.8-7.6 MPa, and a water permeability coefficient of 4.5-8×10 -2 cm / s, compressive strength is 55-85MPa, and wear-resistant wear pit length is 18.4-19.7mm.
4. A method for preparing a high-strength and high-weatherability ecological permeable brick according to any one of claims 1 to 3, comprising the following steps: S1: preparing ceramic particles: crushing and high-energy ball milling the waste ceramic bricks in sequence, and then screening out ceramic particles with an average particle size of 12 to 50 μm for use; S2: preparing ceramic particle clusters: preparing the ceramic particles obtained in S1 into a ceramic slurry, then obtaining a ceramic particle cluster green body by a spray granulation method, and then performing a primary sintering at a high temperature to obtain a ceramic particle cluster; S3: preparing a sintering aid: firstly preparing titanate with high titanium slag, NaOH and 200 parts of tap water as raw materials, and then preparing a sintering aid with titanate, siderite, tap water and HCl solution as raw materials; S4: Preparation of fired permeable bricks: After uniformly mixing ceramic particle clusters, sintering aids, polyvinyl alcohol and tap water, put them into a mold for pressing to obtain permeable brick blanks, and then perform secondary sintering after drying to obtain high-strength and high-weather-resistant ecological permeable bricks.
5. The method for preparing a high-strength and high-weatherability ecological permeable brick according to claim 4, characterized in that: The preparation method of the ceramic slurry in step S2 is: by weight, 80 to 120 parts of ceramic particles, 5 to 15 parts of polyvinyl alcohol adhesive, 15 to 30 parts of AlCl3, 5 to 10 parts of NaOH, 2 to 6 parts of sodium dodecylbenzene sulfonate, 1 to 3 parts of nickel chloride and 10 to 20 parts of tap water are mixed evenly to obtain ceramic slurry.
6. The method for preparing a high-strength and high-weather-resistant ecological permeable brick as described in claim 5, wherein the mass ratio of AlCl3 to NaOH is 3:
1.
7. The method for preparing a high-strength and high-weatherability ecological permeable brick according to claim 4, characterized in that: The parameters of the spray granulation method of the ceramic slurry in step S2 are: the spray granulation inlet temperature is 220-280°C, the outlet temperature is 200-220°C, the rotation speed of the centrifugal atomizer is 2500-9000r / min, and the drying chamber temperature is 210-280°C.
8. The method for preparing a high-strength and high-weather-resistant ecological permeable brick according to claim 4, characterized in that: The parameters of the initial sintering in step S2 are: the ceramic particle cluster green body is sintered in an air atmosphere using a pressureless sintering technology, the temperature is raised from room temperature to 180-240° C. and kept for 1-2 hours, and then the temperature is further raised to 900-1000° C. and sintered for 3-6 hours to obtain a ceramic particle cluster.
9. The method for preparing a high-strength and high-weatherability ecological permeable brick according to claim 4, characterized in that: The parameters of the secondary sintering in step S4 are: pressureless sintering, a sintering temperature of 1150-1300° C., a sintering time of 5-10 hours, and cooling to room temperature after sintering to finally obtain high-strength and high-weatherability ecological permeable bricks.
Citation Information
Patent Citations
Ecological permeation ceramic tile and production method thereof
CN107162566A
Porous ceramic and preparation method thereof
CN116813367A
